Faktor kontribusi kecerdasan pelbagai dalam kalangan pelajar remaja - Siti Rahayah Ariffin,; Roseni Ariffin,; Hafsa Mohamed Makki, (penerbit ukm, 2008)
The Theory of Multiple Intelligences has been widespread in the country’s higher institution of learning through many revised curriculum courses. Previous study shows that Intelectual Quotient (IQ) of each individual only focus on verbal-linguistic and logic-mathematical intelligence. The aim of this study is to determine the contribution of other intelligences toward the two stated intelligences domain. A total of 844 students from the state of Selangor were randomly chosen as samples in this study. This study employed Malaysian Multiple Intelligences Checklist for Adult (MyMICA) which consist of 80 perception items that presented nine domains of multiple intelligences. Findings of the study based on multiple regression analysis showed that interpersonal and logic-mathematical intelligences are some of the intelligences that contribute to the verbal-linguistic intelligence. Logic-mathematical intelligence receive some of the contributions from verbal-linguistic and intrapersonal intelligences.